2019
DOI: 10.12688/f1000research.17148.2
|View full text |Cite
|
Sign up to set email alerts
|

It’s the network, stupid: a population’s sexual network connectivity determines its STI prevalence

Abstract: There is little consensus as to why sexually transmitted infections (STIs), including HIV and bacterial vaginosis (BV) are more prevalent in some populations than others. Using a broad definition of sexual network connectivity that includes both structural and conductivity-related factors, we argue that the available evidence suggests that high prevalence of traditional STIs, HIV and BV can be parsimoniously explained by these populations having more connected sexual networks. Positive feedback, whereby BV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 122 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…35 This segregation has been linked to high rates of STI among the Black community, which low health care quality, sexual networks, and health care utilization may partially explain. [36][37][38] Physician shortages, less experienced physicians, inadequate access to critical care services, fewer specialty referrals, and inadequate access to pharmacies for STI partner therapy are higher in segregated neighborhoods. [39][40][41][42] Segregated sexual networks and selection of sexual partners (eg, number, timing, concurrency) can sustain and restrict STIs within certain racial or ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 This segregation has been linked to high rates of STI among the Black community, which low health care quality, sexual networks, and health care utilization may partially explain. [36][37][38] Physician shortages, less experienced physicians, inadequate access to critical care services, fewer specialty referrals, and inadequate access to pharmacies for STI partner therapy are higher in segregated neighborhoods. [39][40][41][42] Segregated sexual networks and selection of sexual partners (eg, number, timing, concurrency) can sustain and restrict STIs within certain racial or ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Segregated sexual networks and selection of sexual partners (eg, number, timing, concurrency) can sustain and restrict STIs within certain racial or ethnic groups. 36,43 In addition, structural racism has led to policies contributing to high Black male incarceration rates. 44,45 Furthermore, structural exclusion of neighborhoods from opportunity structures based on racial composition of residents can contribute to limited community resources, inadequate social support, and strengthened social stigma or medical mistrust, 46 all of which can lead to poor health care utilization and delayed treatment for STIs.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is an increasing appreciation that a population’s sexual network connectivity is a key determinant of the equilibrium prevalence of an STI in that population. 15 Thus, individuals in a HIV preexposure prophylaxis (PrEP) cohort typically report a mean of five or more partners per 3 months and typically have a gonorrhoea prevalence of around 10%. 10,16 If the intense use of antimicrobials in this population (via screening or doxycycline PEP), lowers the prevalence to 5% but only for as long as the intervention persists, then this implies that the intervention has kept the prevalence at roughly half the equilibrium prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of syphilis in men who have sex with men (MSM) in the United States (USA), for example, was high in the 1970s, but declined dramatically in the early 1980s only to return to 1970s levels more recently ( Figure 1 ) 7 . In this paper we test the hypothesis that differences in the connectivity of local sexual networks play an important role explaining these cross sectional and longitudinal variations in STI incidence 8 , 9 . Although the connectivity of local sexual networks is determined by a number of parameters, we focus on two of the most important - the rate of partner change and the proportion of partnerships that run concurrently 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we test the hypothesis that differences in the connectivity of local sexual networks play an important role explaining these cross sectional and longitudinal variations in STI incidence 8 , 9 . Although the connectivity of local sexual networks is determined by a number of parameters, we focus on two of the most important - the rate of partner change and the proportion of partnerships that run concurrently 8 , 9 . Previous analyses have typically found that one, or a combination of markers of network connectivity, are raised in populations with a higher prevalence of a particular STI 3 , 4 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%